Vaginal birth after caesarean section: why and how? - Bangal, Vidyadhar B.; Gavhane, Satyajit; Yadav, Vishesha; Aher, Kunal; Bhavsar, Dhruval (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: With the significant rise in the incidence of primary caesarean section(CS) for various indications, an increasing proportion of the pregnant women coming for antenatal care, report with a history of a previous CS. This necessitates definite need to bring down the caesarean section rate, either by judicious selection of cases for primary caesarean section or by attempting vaginal delivery, following previous caesarean section (VBAC). Methods: A prospective observational study was conducted to find out the success of VBAC and the common predictive factors leading to successful VBAC. A total of 136 pregnant women with full term pregnancy, having history of previous one lower segment caesarean section and without any other medical and obstetrical complication were enrolled in the study. Results: Majority of the women (95.59%) had spontaneous onset of labor. The success of VBAC was 75 percent. The commonest maternal complications were fever (7.35%), scar dehiscence (3.68%), PPH (1.47%) and wound infection (2.21%).There was significantly higher number of women who had history of previous successful VBAC, had vaginal delivery (91.67%; p=0.038).It was observed that the rate of vaginal delivery was significantly high in women with Bishop’s score between 10 to 13 (94.64%) compared to 6 to 9 (61.25%) (p<0.001).The baby weight determined by ultrasound scan was significantly associated with mode of delivery (p=0.049). Conclusions: Vaginal Birth After Caesarean section is relatively safe, provided it is conducted in carefully selected cases, under constant supervision. Spontaneous onset of labour, good Bishops score and average baby weight were good predictors of successful VBAC.